Influence of an Inquiry-Based Learning Model on Maternal Behavior in Response to Diarrhea in Children under the Age of Five Years at the Tempe Health Center, Wajo Regency, Indonesia - Nyorong, Mappeaty; Burhan, Hamzah (Pakistan Journal of Nutrition, 2015)
Diarrhea remains a cause of death in children under the age of five years around the world. This research study aimed to analyze the influence of an inquiry learning model on maternal behavior in response to diarrhea in children under the age of five years at the Tempe Health Center, Wajo Regency. This research was a quasi-experiment with a randomized pre-test post-test control group design and was performed at the Tempe and Pitumpanua Health Centers, Wajo Regency. The study population consisted of mothers with children under age five that suffered from diarrhea and the sample size was 60 respondents. Samples were chosen by simple random sampling. Data collection was performed using questionnaires. The data were analyzed using paired t-tests, Wilcoxon signed-rank tests, independent sample t-tests and Mann-Whitney U-tests. The results of this study indicate that an inquiry learning model influenced the response of mothers to diarrhea in children under the age of five years at the Tempe Health Center, with a significant change in the average knowledge score and attitude score of the mothers in the intervention and control groups (differences of 29.26 and 12.67, respectively). The practice of training mothers in the application of oral rehydration therapy generated a difference of 15.5 between the average practice scores of the control and intervention groups. These findings suggest that an inquiry learning model is more effective at improving maternal behavior in response to diarrhea in children under age five at the Tempe Health Center, Wajo Regency.